2020
DOI: 10.1136/heartjnl-2020-317701
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal pro-brain natriuretic peptide and sudden cardiac death in hypertrophic cardiomyopathy

Abstract: ObjectiveElevated levels of N-terminal pro-brain natriuretic peptide (NT-proBNP) are associated with heart failure-related death in hypertrophic cardiomyopathy (HCM), but the relationship between NT-proBNP level and sudden cardiac death (SCD) in HCM remains undefined.MethodsThe study prospectively enrolled 977 unrelated patients with HCM with available NT-proBNP results who were prospectively enrolled and followed for 3.0±2.1 years. The Harrell’s C-statistic under the receiver operating characteristic curve wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
1
15
2
Order By: Relevance
“…Thus, the results are valuable and cannot be accidental. However, no significant differences were observed in the incidence of SCD and HFRD in the present study, which is different from previous results [11,26]. And compared with previous studies [11,27], higher mortality was observed in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Thus, the results are valuable and cannot be accidental. However, no significant differences were observed in the incidence of SCD and HFRD in the present study, which is different from previous results [11,26]. And compared with previous studies [11,27], higher mortality was observed in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed NT-proBNP remained an independent predictor of ACD and CD after adjusting for these confounders. In addition, the results were consistent with a previous report [11]. Thus, the results are valuable and cannot be accidental.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…LVEF was calculated from two-dimensional echocardiography images using the modified Simpsons rule formula. NT-proBNP concentrations were measured as described in our previous study [ 9 ]. Specifically, venous blood samples were collected into serum separator tubes by direct venipuncture and sent to the laboratory for testing.…”
Section: Methodsmentioning
confidence: 99%